Relationship between tree circumference and arboreal ants community (Hymenoptera: Formicidae) in a protected area in the Amazon - Andrade-Silva, Joudellys; Almeida, Rony Peterson Santos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The mechanisms responsible for the coexistence of species in the environment have considerable implications in the structuring of local fauna. We aim to evaluate the structure of the ant community in a protected area in the Amazon rainforest, using trees circumference as a parameter of environmental heterogeneity. We conducted this experiment on 29 trees from different circumferences (from 11 cm to 234 cm), and captured the ants using pitfall traps with human urine. We found 30 ant species, but the tree circumference did not influence either the richness or the composition of ants. Studies on combined factors and more directly associated with environmental heterogeneity, such as the connectivity of trees, must be carried out so that we can understand the local drivers of diversity in the vertical stratum of preserved Amazon forest remnants.
Keywords: Preserved environments; Caxiuanã National Forest; Vertical stratum; Brazilian Amazon; Neotropical ants